Pendidikan Al-Qur’an Dalam Membentuk Karakter Religius Di Era Pandemi Covid-19 Di Tpq Darul Fataa Dusun Balungombo Desa Tembelang Kecamatan Tembelang - Zaeni, Akhmad; Hariyanto, Ahmad Muhammad (AS-SUNNIYYAH, 2021)
The implementation of a work program in the form of mentoring the youth activities of Al-Hasan mosque balungombo village tembelang tembelang district of Jombang district as a bridge in achieving an organizing goal, unifying youth harmony in building a relationship with the local community through the educational activities of the Qur'an during the covid-19 pandemic. The partner of this community service activity is the Youth Association of Masjid Al-Hasan balungombo village Tembelang sub-district of Tembelang Jombang Regency. The background of this devotion is the importance of a teenage person in the introduction of the law of tajwid science as well as improving reading in reading the Holy Qur'an early on by always improving the makhorijul of letters. The purpose of this community service activity is to unify the relationship between the youth in Balungombo village tembelang tembelang sub-district of Jombang district, and to add santri knowledge about tajwid science and improve the makhorijul letters to the youth of Al-Hasan mosque balungombo village to the Education of the Qur'an. The method used in this devotion is the first, bottom up approach using "participation". The approach does not depart from the outside but from the inside. A set of problems and needs are formulated together, a number of values and systems are understood together. The second is that when applying the reading method to the Qur'an many adolescents have difficulty reading, choking, and loss of concentration, then a researcher immediately takes a step. The way to re-focus the youth on props. The goal is to better understand the concept, and know where the difficulties are.